State Bar of California Annual Meeting Held at Century Plaza Hotel - Watkins, Howard::::::::: (1987)
Fresno County Bar Association delegation Doris Coleman, Michael J. F. Smith, Herbert Levy, William J. Smith, Robert Oliver, and Judy Soley; in front Peter Kuetzing